دور القاضي بين تطبيق القانون وتحقيق العدالة - موسى الهبريد. عبير محمد (Aljameai, 2026)
المستخلص: يهدف البحث إلى توضيح الدور الذي يلعبه القاضي عند الحكم في القضايا المعروضة أمامه . وهل فعلا هو محقق للعدالة أم إنه مجرد مطبق لنصوص القانون؟ والتي يحب أن تكون محققة للعدالة بطريقة فلسفية قانونية ، كما يهدف البحث إلى توضيح التفرقة بين مفهوم العدل والعدالة وعلاقتها بالقانون وأهدافه، كما يهدف البحث أيضا إلى بيان دور كل من القاضي الجنائي والقاضي المدني في تطبيق القانون ومن ثم تحقيق العدالة. وتبدو أهمية البحث في احترام سيادة القانون فهو الأساس في إرساء مبادئ العدالة من خلال المساواة بين الناس التي تقف أمام القانون وتخضع لأحكامه وقد اتبعنا المنهج الفلسفي التحليلي المقارن بين القانون المدني والقانون الجنائي. وتوصلنا من خلال البحث إلى أن الأمر نظريا، يحتاج إلى المواءمة بين دور القاضي في تحقيق العدالة من خلال تطبيق القانون فدور القاضي في تحقيق العدالة دور أساسي يتجاوز تطبيق القانون فهو مترجم للقانون ومسؤول عن ضمان نزاهة الاجراءات ومُحكِم في الأدلة وصانع قرار عادل، ولكي يُرسي العدالة فهو يسعى إلى تطبيق القانون ، فلا عدالة خارج إطار القانون ولا يتصور تطبيق القانون دون عدالة. أما عمليا، فالدور الاكبر يقع على عاتق السلطة التشريعية فهي التي يجب أن تحرص على تحقيق العدالة من خلال الصياغة القانونية الجيدة للنصوص التشريعية التي تضمن بدورها تحقيق العدالة عند تطبيق القانون. Abstract: This research aims to clarify the role of the judge when ruling on cases brought before him. Is he truly an achiever of justice, or merely an implementer of legal texts that should ideally achieve justice through a philosophical and legal approach? The research also aims to clarify the distinction between the concepts of justice and equity, and their relationship to law and its objectives. Furthermore, it seeks to explain the roles of both the criminal and civil judges in applying the law and, consequently, achieving justice. The importance of this research lies in upholding the rule of law, which is fundamental to establishing the principles of justice through equality before the law and subjection to its provisions. We have adopted a comparative analytical philosophical approach, examining civil and criminal law. Through our research, we concluded that, theoretically, the judge’s role in achieving justice through the application of the law needs to be reconciled. The judge’s role in achieving justice is fundamental and goes beyond the application of the law. He is an interpreter of the law, responsible for ensuring the integrity of procedures, an arbiter of evidence, and a fair decision-maker. In order to establish justice, he seeks to apply the law. There is no justice outside the framework of the law, and the application of the law is inconceivable without justice. Practically, the greatest role falls on the legislative authority, which must ensure the achievement of justice through good legal drafting of legislative texts that, in turn, guarantee the achievement of justice when applying the law.